3(2x+7)=6(x+)-3

Simple and best practice solution for 3(2x+7)=6(x+)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+7)=6(x+)-3 equation:



3(2x+7)=6(x+)-3
We move all terms to the left:
3(2x+7)-(6(x+)-3)=0
We add all the numbers together, and all the variables
3(2x+7)-(6(+x)-3)=0
We multiply parentheses
6x-(6(+x)-3)+21=0
We calculate terms in parentheses: -(6(+x)-3), so:
6(+x)-3
We multiply parentheses
6x-3
Back to the equation:
-(6x-3)
We get rid of parentheses
6x-6x+3+21=0
We add all the numbers together, and all the variables
24!=0
There is no solution for this equation

See similar equations:

| (a+2)(a+1)=0 | | -3m+9=6m-18 | | x=3D=5x²-10 | | A=(x+2)*(x+2) | | 9w+6w-8w-5=16 | | 1/5x*5=19-1/2x | | 10x-5=8x-2x+7-2 | | -5x+12=5x-5) | | x=-1C=10-8x | | 15/x=45/18 | | x-(x/4)-55=500 | | (-8.7)(1.4)=a | | (18+7)d=400=5d | | 6(x=3)=36 | | 8x-16=4x+24 | | 85+36+x=180 | | 9w+6w-5=16 | | x=3B=25-5x | | -5+15y=-5y+35 | | 2/3x+5=2x-11 | | 90+10+x=180 | | 3x=-9.6 | | 5(d+7)=4(d-8) | | (8x-23)+(7x-7)=90 | | 85+59+x=180 | | A=(x+2)2 | | 36x2=85 | | 4.28x+25.68=51.36 | | 6(4+a)=96a= | | x=2A=4x+3 | | x/12=54/72 | | 6+10=8x+12 |

Equations solver categories